A survey on energy efficiency in mobile ad hoc networks - Shirly, Geofrin; Kumar, N (International Journal of Engineering and Technology, 2018)
A mobile ad-hoc network is a collection of wireless mobile nodes which temporarily forms a network without any type of centralized administration which is already in use. In adhoc network, the battery lifetime of the mobile nodes is less. If suppose any nodes battery power is drained it leads to spreading of many divisions in the networks. Hence these spreader nodes are the very important spot in this network. For the purpose of data forwarding some very important nodes can drain their battery power in advance because of increase in load and processing for forwarding the data. Because of the variance in loads developed, the network of nodes will be collapsed very badly, the route lifetime will be reduced, network will be partitioned and route reliability is reduced in MANETs. Because of this, the most important criteria which have to be improved is the consumption of energy in mobile ad-hoc networks. The very important technique is power aware routing technique in MANETs. Hence minimization of energy in the network of mobile nodes individually can be done by using some of the routing techniques. The most important thing is to study the power aware protocol in order to help the new research doers and application developers to find a new idea for designing more efficient routing protocols.Â Â